2023
DOI: 10.1021/jacs.3c05080
|View full text |Cite
|
Sign up to set email alerts
|

Circularly Polarized Light-Dependent Pyro-Phototronic Effect from 2D Chiral–Polar Double Perovskites

Zhou Li,
Chengmin Ji,
Yipeng Fan
et al.

Abstract: Chiral hybrid perovskites combine the advantages of chiral materials and halide perovskites, offering an ideal platform for the design of circularly polarized light (CPL) detectors. The pyro-phototronic effect, as a special mechanism of the photoexcited pyroelectric signal, can significantly improve the performance of photodetectors, whereas it remains a great challenge to achieve pyroelectricity-based CPL detection. In this work, the chiroptical phenomena and the pyro-phototronic effect are combined in chiral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…[9][10] Recent studies revealed that hybrid metal halides are among the most promising candidates for CPL-active materials, due to their high efficiency, simple synthesis, and great structural versatility. [11][12][13] The strategy of integrating chiral components with metal halides can unlock the manifold peculiar properties such as CPL, [14][15] ferroelectricity, [16][17] secondharmonic generation, [18] and magnetism. [19] Although hybrid metal halides can serve as a good model system for designing novel CPL active materials, [20][21][22][23] achieving both high photoluminescence quantum yield (PLQY) and large luminescence asymmetry factor (g lum ) remains a great challenge, and such high-performance CPL-emitting materials are still rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10] Recent studies revealed that hybrid metal halides are among the most promising candidates for CPL-active materials, due to their high efficiency, simple synthesis, and great structural versatility. [11][12][13] The strategy of integrating chiral components with metal halides can unlock the manifold peculiar properties such as CPL, [14][15] ferroelectricity, [16][17] secondharmonic generation, [18] and magnetism. [19] Although hybrid metal halides can serve as a good model system for designing novel CPL active materials, [20][21][22][23] achieving both high photoluminescence quantum yield (PLQY) and large luminescence asymmetry factor (g lum ) remains a great challenge, and such high-performance CPL-emitting materials are still rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…The pyro-phototronic effect, which involves the interplay of pyroelectricity, photoexcitation, and semiconductors, has recently been utilized in the development of self-powered PDs based on ferroelectric MHPs. However, the utilization of the pyro-phototronic effect in nonpolar perovskites is frequently constrained. Recent findings have indicated that centrosymmetric materials possess the capability to manifest pyroelectricity at the interface with alternative materials.…”
Section: Introductionmentioning
confidence: 99%
“…8,14 Inescapably, the lead element would cause irreversible damage to the environment and the human body, which severely limits the application prospects of lead-based photocatalysts in PCR reactions. Comparatively, bismuth( iii )-based hybrid halides provide a nontoxic lead-free alternative for many applications such as photocatalysis, 15–17 photovoltaics 18,19 and radiation detection, 20,21 because bismuth( iii ) possesses a similar electronic structure and 6s 2 inert pair effect to those of lead( ii ). Dismayingly, the reported hybrid bismuth( iii ) halides mostly contain typical hydrogen-bond donors, e.g.…”
Section: Introductionmentioning
confidence: 99%